Mechanisms and Evolutionary Patterns of Mammalian and Avian Dosage Compensation - Julien, Philippe; Brawand, David; Soumillon, Magali; Necsulea, Anamaria; Liechti, Angélica; Schütz, Frédéric; Daish, Tasman; Grützner, Frank; Kaessmann, Henrik (PLOS Biology, 2012)
A large-scale comparative gene expression study reveals the different ways in which the chromosome-wide gene dosage reductions resulting from sex chromosome differentiation events were compensated during mammalian and avian evolution.